The mutant project : inside the global race to genetically modify humans - Kirksey, Eben, 1976- (Bristol University Press, 2021)
An anthropologist visits the frontiers of genetics, medicine, and technology to ask: whose values are guiding gene-editing experiments, and what are the implications for humanity?